1996
DOI: 10.1590/s0006-87051996000200003
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de parentais e híbridos entre Vitis vinifera e Vitis rotundifolia utilizando polimorfismo enzimático e marcador RAPD

Abstract: Identificaram-se parentais e híbridos entre Vitis vinifera (videiras comuns) e V. rotundifolia (muscadínias), utilizando-se o polimorfismo enzimático e marcador RAPD (Random Amplified Polymorphic DNA). Os sistemas GOT (glutamato-oxalo-acetato-transaminase), IDH (isocitrato desidrogenase) e PGI (fosfoglucose isomerase) diferenciaram a muscadínia, sendo observadas cinco aloenzimas para o GOT, duas para o LAP (leucina aminopeptidase) e quatro para o EST (esterase). Os sistemas PGI e IDH apresentaram-se como dimér… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…4). Similar results were reported by Royo et al (1994) and Sawazaki et al (1996), who observed that only the GOT system of Vitis vinifera demonstrated band migration diversity, with some bands advancing or delaying in relation to the others. These same authors suggested that this diversity might only be associated with migration speed, as genetic crossings to confi rm Mendelian inheritance were not carried out.…”
Section: Resultssupporting
confidence: 90%
“…4). Similar results were reported by Royo et al (1994) and Sawazaki et al (1996), who observed that only the GOT system of Vitis vinifera demonstrated band migration diversity, with some bands advancing or delaying in relation to the others. These same authors suggested that this diversity might only be associated with migration speed, as genetic crossings to confi rm Mendelian inheritance were not carried out.…”
Section: Resultssupporting
confidence: 90%